Pengaruh Service Quality dan Empathy terhadap Purchase Intention di Pasar Tradisional Melalui Word of Mouth: - Ida Bagus Nyoman Udayana; Rejeki Sekar Dwifa (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Purchase intention or purchase intention is something that is directly related to prospective buyers. This cannot be separated from the prospective buyers themselves who will decide to buy what is offered or not. This purchase intention can be influenced by several things, such as service quality, empathy, and word of mouth. All three have their respective roles in influencing a person's purchase intention. Departing from this statement, the author conducted a study with traditional markets as the object of this research, especially traditional markets in the Bantul Regency area. The objectives of this study are (1) whether service quality has an effect on WOM on purchase intention in traditional markets in Bantul Regency, (2) whether empathy has an effect on WOM on purchase intentions in traditional markets in Bantul Regency, (3) whether WOM has an effect on purchase intention in traditional markets in Bantul Regency. In this study service quality and empathy as independent variables, which will affect the dependent variable indirectly through the intervening variable. While word of mouth as an intervening variable that will be influenced by the independent variable and will affect the dependent variable directly. The results of this study indicate that service quality and word of mouth have a positive and significant effect on purchase intention. While empathy has a negative and insignificant effect on purchase intention through word of mouth. Keywords: service quality, empathy, word of mouth, and purchase intention.